1967
DOI: 10.3109/00016486709128786
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Auris Associated with Facial Nerve Palsy and Auditory Nerve Symptoms: A Case Report with Histopathological Findings

Abstract: A typical case of herpes zoster auris is described. Sections of the teniporal bone of tlie clinically affected side show extensive lynipliocytic or round cell infiltration of the facial nerve throughout its length and of the auditory nerve. There is considerable perivascular "cuffing" by lymphocytes in tlie modiolus, in the perineural tissue of the facial nerve, the cliorda tympani and the skin of the external auditory meatus.The vestibular, spiral and geniculate ganglia contain numerous normallooking neurones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Aleksic et al [4] subsequently reported histopathologic alterations in the geniculate ganglion, while Denney-Brown et al [3] found a normal geniculate ganglion, and suggested that a lower motor neuritis might be the cause of the facial nerve palsy. In 1967 Backley et al [21] reported diffuse pathological changes extensively involving the Fallopian canal and suggested the presence of suprageniculate and transgeniculate nervous anastomoses as the route of inflammation to the vestibular and cochlear nerves. Finally, in 1983 Etholm and Schuknecht [5] found degeneration of the facial, cochlear and vestibular nerve trunks in the IAC, but a normal geniculate ganglion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aleksic et al [4] subsequently reported histopathologic alterations in the geniculate ganglion, while Denney-Brown et al [3] found a normal geniculate ganglion, and suggested that a lower motor neuritis might be the cause of the facial nerve palsy. In 1967 Backley et al [21] reported diffuse pathological changes extensively involving the Fallopian canal and suggested the presence of suprageniculate and transgeniculate nervous anastomoses as the route of inflammation to the vestibular and cochlear nerves. Finally, in 1983 Etholm and Schuknecht [5] found degeneration of the facial, cochlear and vestibular nerve trunks in the IAC, but a normal geniculate ganglion.…”
Section: Discussionmentioning
confidence: 99%
“…This infection may sometimes spread, eventually involving the 8th cranial nerve with resultant tinnitus, hearing loss, and vertigo [21,22]. Varicella zoster is the most common zoster infection affecting the head and neck after herpes zoster ophthalmicus [2], and is the second most common cause of facial paralysis [23].…”
Section: Discussionmentioning
confidence: 99%
“…In ammation of the facial nerve and the appearance of vesicles on the pinna are thought to be induced by reactivation of dormant VZV infection in the geniculate ganglion (3 -5). Temporal bone histopathologic studies of RH syndrome have demonstrated diffuse, pronounced round-cell in ltration in the degenerated intratemporal facial nerve (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In the early stage of RH syndrome, gadoliniumenhanced MRI frequently demonstrates signs of inammation of the facial nerve around the geniculate ganglion (17 -20).…”
Section: Introductionmentioning
confidence: 96%
“…Inflammation of the facial nerve due to reactivation of varicella-zoster virus (VZV) is a known cause of RHS, and perivascular, perineural, or intraneural aggregations of round cells in the facial nerve have been observed in patients with RHS. [1] Neurological complications include changes in cerebrospinal fluids, peripheral motor neuropathy, aseptic meningitis, and cranial polyneuropathy. [2] Among these, vestibulocochlear symptoms such as vertigo, hearing loss, and tinnitus most commonly occur in patients with RHS.…”
Section: Introductionsmentioning
confidence: 99%